Five new species belonging to the genus Prorocentrum to the flora of benthic dinoflagellate of Vietnam - The, Ho Van (Academia Journal of Biology, 2012)
Five benthic dinoflagellate species of genus Prorocentrum (Dinophyta) were identified and described as first records to benthic dinoflagellate flora in Vietnam. They are Prorocentrum maculosum, P. arenarium, P. sculptile, P. tropicalis and P. faustiae. The specimens of these species were collected from seaweeds and seagrasses along the coasts, Truong Sa archipelago, Vietnam. These species are distinguished by a number of morphological characteristics: cell shape and size, surface structure and ornamentation of the valves, apical spine, pyrenoids, nucleus and intercalary band. Cells of P. maculosum are broadly ovate in valve view. Cells are 45-50 mm long and 35-40 mm wide. The thecal surface is rugose with distinct scattered valve poroids. The valve margin of P. maculosum form ridge which appears as a flange around the cell. The marginal pores are present. The right valve has a V- shaped depression in the periflagellar area. Pyrenoid locates in the central cell. Cells of P. arenarium are slightly circular in valve view. Cell size ranges from 33-38 mm in diameter. The thecal surface is smooth and has many poroids (75 - 90 pores per valve) except in the central area. The poroids are kidney-shaped to oblong with an average size of 0.4-0.5 mm long. The marginal pores are present, 55-62 pores per valve. The periflagellar area is a V-shaped depression in the right valve. Cells of P. sculptile are broadly oval in valve view. Both valves are slightly convex. The cell measures 35 - 40 mm in length and 32 - 35 mm in width. The valve surface has shallow depressions of variable shapes. Trichocyst pores are situated in shallow depression on the valve surface. The periflagellar area on the right valve has a deep, asymmetrical, V-shaped indentation. Cells of P. tropicalis are oval in valve view with the maximum width behind the middle region. Cells are 45-50 mm long and 40-45 mm wide. The thecal surface is rugose and has more poroids except in the central region. Poroids are round, and situated in shallow depressions. The cell margin has a ledge, marginal pores absent. The right valve has a deep, symmetrical, V-shaped indentation. Cells of P. faustiae are slightly elongate with a round posterior end. Cells are 50 - 56 mm long, and 42 - 46 mm wide. The thecal surface is rugose and perforated with numerous small, round pores except in the central cell. Each pore is situated in a shallow depression. The periflagellar area on the right valve has a deep, symmetric, V-shaped indentation.